The determination of an effective radius of an optically trapped polystyrene microbead distribution near a water air interface - Muhammad Safuan Mat Yeng@Mat Zin (Tanjong Malim, 2019)
The determination of an effective radius of an optically trapped polystyrene microbead distribution near a water air interface by Muhammad Safuan Mat Yeng@Mat Zin